Модель унифицированного подхода к построению систем автоматизированного контроля и наблюдения - Буртняк, В.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
The model of the compatible going is offered near the construction of the
automated checking and looking systems after radiation materials. Four classes of
elements of standardization are selected. The compatible levels of the system are
considered.